Solving intuitionistic fuzzy fractional differential equations with $ψ$-Caputo fractional derivative - K. Oufkir; H. Sadiki; M. Elomari (Researches in Mathematics)
In this research paper, we have attempted to establish the definition of the fractional derivative $ψ$-Caputo, the $ψ $-fractional integral, and the $ψ$-Laplace transform in the fuzzy intuitionistic sense, along with their properties. Furthermore, our objective is to explore the existence and uniqueness of solutions for certain intuitionistic fuzzy fractional differential equations (IFFDE) under the $ψ$-Caputo derivative of order $q \in (0,1)$. Lastly, we present an application example at the end to demonstrate how these findings can be applied in practice.